Behaviourally modern humans in coastal southern Africa experienced an increasingly continental climate during the transition from Marine Isotope Stage 5 to 4 - Göktürk, Ozan Mert; Simon, Margit H.; Sobolowski, Stefan Pieter; Zhang, Zhongshi; Van Der Bilt, Willem; Mørkved, Pål Tore; D’Andrea, William J.; van Niekerk, Karen L.; Henshilwood, Christopher S.; Armitage, Simon J.; Jansen, Eystein (Frontiers in Earth Science, 2023)
Linking human technological and behavioural advances to environmental changes is challenging, as it requires a robust understanding of past climate at local scales. Here, we present results from regional high-resolution numerical simulations along with climate data directly from the archaeological sequence of Blombos Cave (BBC), a well-studied site in coastal southern Africa. The model simulations cover two distinct periods centred at 82 and 70 thousand years (ka) ago (Marine Isotope Stage [MIS] 5 and the onset of MIS4, respectively), when orbital parameters and global sea level were markedly different from one another. Climatic changes from 82 to 70 ka are determined through four simulations that use past and present-day coastline configurations. The hydrogen isotopic composition of leaf waxes (δ2Hwax) and n-alkane distributions and abundances are used to reconstruct hydroclimate around BBC. The leaf wax n-alkane record, one of the first produced in an archaeological setting in this region to date, can be interpreted as a drying signal from MIS 5c to 4. This agrees with our modelling results, which indicate a drier and more continental climate over coastal southern Africa at 70 ka, compared to 82 ka. The simulated aridification is most evident from the reduced precipitation amounts in both summer (~20%) and winter (~30%). The annual number of summer days (Tmax ≥ 25°C) and cold nights (Tmin < 5°C) in the vicinity of BBC increases more than 5 and 3-fold, respectively, under the more continental climate at 70 ka. Weaker westerly winds in winter, a cooler Agulhas Current, and a land surface expansion associated with the coastline shift due to lower sea levels at 70 ka all contribute to the simulated climate shift. Our approach highlights the importance of multiple lines of evidence for achieving robust results, while demonstrating how both large-scale forcing and local influences worked together in shaping the local climate that early humans lived in. Adaptation to a drier climate and increased continentality around BBC might have induced greater mobility, which led to increased population interactions, cultural transmission rates, skill exchange, and material complexity during the so-called Still Bay period.